Numerical Modelling, Simulation, and Analysis of the End-Milling Process Using DEFORM-3D with Experimental Validation - B. Deepanraj; N. Senthilkumar; G. Hariharan; T. Tamizharasan; Tesfaye Tefera Bezabih (Advances in Materials Science and Engineering)
In this present work, finite element analysis (FEA)-based simulation of end-milling of AISI1045 steel using tungsten carbide tool was performed using DEFORM-3D simulation software. Usui tool wear model, Johnson-cook material model and adaptive remeshing are considered during machining simulation. The impact of machining variables rate of feed, tool speed, and depth of cut was investigated, and the best integration of variables was distinguished for lower cutting temperature, principal stress, cutting forces, effective stresses, tool wear, and effective strain. The obtained results were correlated using experimentation in a vertical machining center attached with a Kistler tool dynamometer with data acquisition setup for capturing the cutting forces, and an infrared (IR) thermometer was used to measure the cutting temperature, and a comparison was done. Results showed a good correlation. There is a relationship between experimental and numerical results, and simulation findings can be utilised for interpreting the influence of machining parameters.